2009
DOI: 10.3233/jad-2009-1161
|View full text |Cite
|
Sign up to set email alerts
|

Differential Patterns of Implicit Emotional Processing in Alzheimer's Disease and Healthy Aging

Abstract: Implicit memory for emotional facial expressions (EFEs) was investigated in young adults, healthy old adults, and mild Alzheimer's disease (AD) patients. Implicit memory is revealed by the effect of experience on performance by studying previously encoded versus novel stimuli, a phenomenon referred to as perceptual priming. The aim was to assess the changes in the patterns of priming as a function of aging and dementia. Participants identified EFEs taken from the Facial Action Coding System and the stimuli use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 56 publications
2
15
0
1
Order By: Relevance
“…This findings agree with those from previous studies on the recognition of facial expressions, in which a happy face was most easily recognized cross-culturally (both Japanese and Caucasian) [15] among both healthy people and elderly subjects with AD [7, 12, 16, 17], as well as people with severe dementia [8]. In addition, the coefficient of correlation between the MMSE and Anger scores (r = 0.434) tended to be higher than that between the MMSE and Smile scores (r = 0.346).…”
Section: Discussionsupporting
confidence: 92%
“…This findings agree with those from previous studies on the recognition of facial expressions, in which a happy face was most easily recognized cross-culturally (both Japanese and Caucasian) [15] among both healthy people and elderly subjects with AD [7, 12, 16, 17], as well as people with severe dementia [8]. In addition, the coefficient of correlation between the MMSE and Anger scores (r = 0.434) tended to be higher than that between the MMSE and Smile scores (r = 0.346).…”
Section: Discussionsupporting
confidence: 92%
“…These authors suggested that implicit affective dispositions were relatively intact in dementia. Similarly, preservation of emotional priming in AD has been suggested, since emotional categorization was more accurate for previous emotional priming than for neutral priming (Labar et al, 2005; Garcia-Rodriguez et al, 2009). On the other hand, AD patients have presented deficits in the acquisition of fear conditioning responses, although normal reactivity to the aversive stimulus was found (Hamann et al, 2002; Hoefer et al, 2008).…”
Section: Emotional Effects On Preserved and Impaired Memories In Alzhmentioning
confidence: 84%
“…These emotional influences have not, however, been associated with an EEE, as no strict assessment of memory performances has been done that compared an emotional with a neutral stimulus. Several AD studies have investigated memory implicitly in the context of affective learning (Blessing et al, 2006, 2010), emotional priming (Quoniam et al, 2003; Labar et al, 2005; Garcia-Rodriguez et al, 2009), and fear conditioning (Hamann et al, 2002; Hoefer et al, 2008). The study of Blessing and coworkers (2006) showed that patients’ affective ratings of neutral faces were systematically altered by the biographical information (pleasant or aversive stories) that was previously associated with the face.…”
Section: Emotional Effects On Preserved and Impaired Memories In Alzhmentioning
confidence: 99%
“…The capacity to identify EFEs can be confounded with general cognitive abilities, such as attention [21][22][23], working memory [24][25][26][27] and visuo-spatial skills. Indeed, it has been suggested that all types of facial recognition, with or without emotional content, are dependent upon visuo-spatial resources [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%